Florida Soil Series and Natural Community Associations - G. D. J. LaPierre; N. D. Medina Irizarry; M. G. Andreu (EDIS)
Soils often dictate the presence of different types of inherent natural communities. In this project we created a table that relates soil series to natural communities found in Florida. Correlation of soil series and natural communities was performed through the synthesis of land management plans, the Florida Natural Areas Inventory (FNAI) documentation of exemplary sites, along with the UC Davis Soil Resource Laboratory Soil Web Survey mapping information system (SoilWeb). The GPS coordinates and conservation site names of the selected locations for said soil series are also recorded in this table. Use of this table can help private landowners, land managers, and researchers detect current and former natural communities on sites.